Phytochemical and Neuropharmacological Evaluation of Banisteriopsis caapi, Paullinia cupana, and Turnera diffusa for Potential Anti-Addiction Activity - Fernando Benevenuto; Iscia Martha Franco; Antonio Eizirik; Loureiro Gilberto; Adriana Martinez (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
Addiction remains a major neuropsychiatric challenge, with dopaminergic, serotonergic, and GABAergic dysregulation underlying maladaptive behaviors. Traditional Brazilian medicinal plants offer a rich source of neuroactive compounds, yet their multi-target mechanisms remain underexplored. This study aimed to evaluate the neuropharmacological potential of harmine, caffeine, and damianin through an integrated computational and experimental approach. Plant materials (Banisteriopsis caapi, Paullinia cupana, Turnera diffusa) were collected, authenticated, and processed using standardized extraction and preparative HPLC purification. Structural characterization was confirmed via NMR spectroscopy. In silico molecular docking targeted D2, 5-HT2A, and GABA-A receptors, complemented by ADMET profiling and network pharmacology simulations. Control ligands; selegiline, haloperidol, and fluoxetine provided pharmacological benchmarks. In vitro assays using HEK293, SH-SY5Y, and HepG2 cells evaluated cytotoxicity and neuroactivity. Docking results revealed harmine as a selective D2 receptor partial agonist (−10.2 kcal/mol), caffeine as a moderate 5-HT2A modulator (−8.1 kcal/mol), and damianin as a GABA-A agonist-like compound (−9.5 kcal/mol). Network simulations suggested synergistic modulation of dopaminergic–serotonergic–GABAergic axes. ADMET predictions indicated favorable BBB permeability, oral bioavailability, and low toxicity, with caution for harmine’s moderate CYP2D6 inhibition. These findings underscore a triadic pharmacodynamic model where dopaminergic stabilization, serotonergic normalization, and GABAergic inhibition collectively mitigate craving and withdrawal symptoms. Future research should integrate receptor-binding validation, in vivo behavioral studies, and clinical pharmacokinetics to translate these computational insights into novel plant-based adjunct therapies for substance dependence. The study provides mechanistic and ethnopharmacological rationale supporting Brazilian botanicals as promising multi-receptor neurotherapeutics.